Adaptive Bandwidth Allocation Strategy under Cloud Platform - Chen, HongLi; Lv, ShanGuo (Informatica, 2015)
With the rapid development of cloud-computing technologies, more and more Internet applications appear with cloud platform. In this paper, cloud computing is introduced. Renting cloud platform which provides computing, storage, bandwidth resources can improve the performance of file sharing systems. The hybrid file sharing system combines P2P mode and cloud serving mode. This system provides both peer-assisted acceleration and cloud-assisted acceleration to download processes. Cloud bandwidth is scalable in the cloud-assisted file sharing system. In order to save cost while meeting QoS requirement, author conducts measurement and analysis on the QQ offline downloading system to find key factors which impact the cloud bandwidth consumption of download process. An adaptive cloud bandwidth rental and allocation strategy is proposed. The experimental results show that the system with this strategy not only ensures the quality of service but also slashed cloud bandwidth consumption.